PENANAMAN NILAI-NILAI PANCASILA MELALUI PEMBELAJARAN BERBASIS PROYEK DENGAN PEMBUATAN POSTER INTERAKTIF MENGGUNAKAN APLIKASI CANVA - Slamet; Ahmad Muhibbin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of project-based learning strategies through the creation of interactive posters using Canva to instill Pancasila values in fourth-grade students at MI Muhammadiyah Wonorejo Gondangrejo. This research employs a qualitative descriptive approach, collecting data through observation, interviews, and document analysis of students' work. The findings indicate that this approach effectively helps students understand Pancasila values, such as tolerance, mutual cooperation, and responsibility, through visualizations in their posters. Additionally, students developed 21st-century skills, including creativity, collaboration, and communication. Despite technical challenges, such as limited digital devices and varying student abilities in using Canva, teachers successfully addressed these issues through personal assistance and efficient device sharing.